Get up and go : strategies for active living after 50 - McDonald, Jim (Dundurn, 2003)
There are many books directed at those who are retired or about to retire, and most of them focus on financial matters, food and nutrition or the best place to settle down. Most fitness books are written for the serious fitness enthusiast, not your average Canadian annuitant. This is a book with a different goal. Get Up and Go motivates those 50 and over to become more physically fit and mentally active. Why? So they can live longer, stay healthy, feel good and enjoy life. And best of all, the authors are speaking from first-hand experience: if it's in the book, it's a reflection of their own personal lifestyle. Whether the reader's main interest is fitness, genealogy, volunteering, crafts, the computer or the learning journey, every chapter is packed with reliable information and interesting tips to help make the most of life.